Epistemic clashes in network science: Mapping the tensions between idiographic and nomothetic subcultures. Issue 2 (August 2020) - Jacomy, Mathieu
This article maps a controversy in network science over the last 15 years, dividing the field about the epistemic status of a central notion, scale-freeness. The article accounts for the two main disputes, in 2005 and in 2018, as they unfolded in academic publications and on social media. This article analyzes the conflict, and the reasons why it reignited in 2018, to the surprise of many. It is argued that (1) the concept of complex networks is shared by the distinct subcultures of theorists and experimentalists; and that (2) these subcultures have incompatible approaches to knowledge: nomothetic (scale-freeness is the sign of a universal law) and idiographic (scale-freeness is an empirical characterization). Following Galison, this article contends that network science is a trading zone where theorists and experimentalists can trade knowledge across the epistemic divide.